2016
DOI: 10.1073/pnas.1604777113
|View full text |Cite
|
Sign up to set email alerts
|

Ultradonut topology of the nuclear envelope

Abstract: The nuclear envelope is a unique topological structure formed by lipid membranes in eukaryotic cells. Unlike other membrane structures, the nuclear envelope comprises two concentric membrane shells fused at numerous sites with toroid-shaped pores that impart a "geometric" genus on the order of thousands. Despite the intriguing architecture and vital biological functions of the nuclear membranes, how they achieve and maintain such a unique arrangement remains unknown. Here, we used the theory of elasticity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 53 publications
(28 reference statements)
1
19
0
Order By: Relevance
“…Consistent with the notion that nuclear membrane tension may have an important role in nuclear membrane structure, a computational approach that minimized bending and stretching energies using the Helfrich-Canham model (Torbati et al, 2016) predicted a decrease in the nuclear membrane separation with an increase in membrane tension. When the membrane was assumed to be under compression (negative tension), the bilayer separation increased significantly, eventually undergoing a bucking instability at a critical compressive stress.…”
Section: Nuclear Bilayer Separationmentioning
confidence: 64%
See 3 more Smart Citations
“…Consistent with the notion that nuclear membrane tension may have an important role in nuclear membrane structure, a computational approach that minimized bending and stretching energies using the Helfrich-Canham model (Torbati et al, 2016) predicted a decrease in the nuclear membrane separation with an increase in membrane tension. When the membrane was assumed to be under compression (negative tension), the bilayer separation increased significantly, eventually undergoing a bucking instability at a critical compressive stress.…”
Section: Nuclear Bilayer Separationmentioning
confidence: 64%
“…If the areal stretch modulus and the bending rigidity of lipid membranes is known, it is possible to calculate their equilibrium shapes under defined geometric constraints (boundary conditions), and under known applied mechanical stresses. This approach has been used to calculate equilibrium shapes of the nucleus and nuclear membranes (Lim et al, 2007;Noguchi, 2016;Torbati et al, 2016), which is discussed in the next section. This approach has also been extensively used to predict the shapes of a diverse array of other lipid membrane structures, such as the membranes of Tensile and shear forces from the cytoskeleton can act on the ONM, and forces from the lamina and/or chromatin can act on the INM.…”
Section: Energetics Of Lipid Membrane Deformationmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2003 ). We have previously shown that a flat shape near the pore necessitates prescription of tension in a membrane lacking curvature-inducing proteins ( Torbati et al. , 2016 ).…”
Section: Resultsmentioning
confidence: 99%